Exploring views on medical care for people with intellectual disabilities: an international concept mapping study - Marian E. J. Breuer; Esther J. Bakker-van Gijssel; Kristel Vlot-van Anrooij; Hilde Tobi; Geraline L. Leusink; Jenneken Naaldenberg (BMC, 2022)
Abstract Background Medical care for people with intellectual and developmental disabilities (IDD) is organized differently across the globe and interpretation of the concept of medical care for people with IDD may vary across countries. Existing models of medical care are not tailored to the specific medical care needs of people with IDD. This study aims to provide an improved understanding of which aspects constitute medical care for people with IDD by exploring how international researchers and practitioners describe this care, using concept mapping. Methods Twenty-five experts (researchers and practitioners) on medical care for people with IDD from 17 countries submitted statements on medical care in their country in a brainstorming session, using an online concept mapping tool. Next, they sorted all collected statements and rated them on importance. Results Participants generated statements that reflect current medical and health care practice, their ideas on good practice, and aspirations for future medical and health care for people with IDD. Based on the sorting of all statements, a concept map was formed, covering 13 aspects that characterize medical and health care for people with IDD across nations. The 13 aspects varied minimally in importance ratings and were grouped into five overarching conceptual themes: (i) active patient role, (ii) provider role, (iii) context of care, (iv) consequences of care for people with IDD, and (v) quality of care. Conclusions The themes, clusters and statements identified through this explorative study provide additional content and context for the specific patient group of people with IDD to the dimensions of previous models of medical care.